The influence of rural amenities on non-metropolitan population change in the United States from, 1980-2000 - Vogel, Harry Landis (Kansas State University, 2006)
The chief aim of this research is to assess the influence of rural amenities on population change amongst all non-metropolitan counties in the United States (excluding Alaska and Hawaii) from 1980 to 2000. Rural amenities, as defined by this research, are the attributes of a non-metropolitan locale that enhance the quality of life of the people living or visiting there. First, I discuss the general patterns of population change in non-metropolitan areas during these three decades as well as the possible influence of rural amenities during this time period. I then examine how rural amenities have been studied by past research in order for me to hypothesize their influence on non-metropolitan population change in the United States. Additionally, I draw on past research in order to guide my conceptualization and measurement of rural amenities. Using data from the United States Census of Population, the National Outdoor Recreational Supply Information System (NORSIS), and David McGranahan’s (1999) Natural Amenity Scale, a panel model data set was constructed for the aforementioned counties from 1980 to 2000. This research constructed a panel data set using data from the aforementioned sources for the years of 1980-2000. Accordingly, in this model the change scores on two measures of population change (absolute population change and percentage population change) were regressed on the amenity and control variables. Regression diagnostics were then used to examine the extent to which specific regression assumptions were validated by the data. Results suggest that climatic amenities, river and ocean based amenities, and warm weather recreational amenities were most significantly associated with increase in population amongst the counties examined by this study.
Keywords: rural; demography; Sociology, Demography (0938)